Competency-Based Human Resource Management: Application for SMES - Yudi Prastiwi, Ni Luh Putu Eka; Widnyani, Ni Made; Adnyani, Luh Ari (Jurnal Ilmiah Manajemen & Bisnis, 2023)
Competency-Based Human Resource Managementincludes Skill, Knowledge and Personal Quality which are closely related to SMES Performance.. This study has the objective of knowing the effect of personal quality on SMES performance moderated by skill and knowledge. The number of workers in the SMES is 50 people who are the respondents who are used as samples in the study. The research design was carried out using an associative quantitative approach with the method of collecting questionnaires and the data analysis technique used was the SmartPLS application. This study states that the parameter coefficient value of the relationship between Personal Quality on SMES Performance is 0.000 and the t-statistic value is 4.567, Personal Quality on SMES Performance which is moderated by skill and knowledge is 0.013 and the t-statistic value is 2.587. It can be stated that all constructs have a positive and significant effect.